Quality Management of the Lalaran Alfiyah Program Based on the PDCA Cycle in Risalah Formal Diniyah Education - Fadlullah, Fadlullah; Helmawati, Helmawati (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to describe and analyze the quality management of the lalaran Alfiyah Ibn Malik program at PDF Ar Risalah, West Bandung Regency, using the PDCA (Plan, Do, Check, Act) framework. The research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and document analysis, then examined using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that program planning was carried out systematically through goal setting, scheduling, the selection of competent musyrif and ustadz, and the preparation of supporting facilities. Program implementation included routine lalaran sessions, memorization submissions, sima’an, habituation practices, and reinforcement of nahwu rule comprehension. Evaluation was conducted through daily, weekly, and monthly mechanisms, while follow-up actions took the form of supplementary coaching, strategy adjustments, and memorization consolidation. The lalaran program was proven effective in improving memorization quality, understanding of Arabic grammatical structures, and students’ discipline. The study concludes that the application of PDCA can optimize kitab kuning learning and serve as a quality development model for pesantren institutions.